MANAGEMENT OF FINANCIAL RESOURCES OF THE ENTERPRISE IN A CRISIS - Tomashevska , A.V; Zhuk , O.I. (The actual problems of regional economy development, 2022)
The purpose of the article is based on the study of theoretical aspects and key features of the formation and management of financial resources of the enterprise in crisis conditions. The following research methods are used in the work: economic analysis, synthesis, logical analysis; scientific abstraction - in highlighting the most important indicators of the "scenario method". The article examines the essence and features of the formation of financial resources of the enterprise in a crisis. It is determined that the financial resources of enterprises play a significant role in the structure of financial relations of society. It is proved that the financial resources of the enterprise are a set of funds in stock, non-fund or material form, which are intended for the fulfillment of financial obligations, the implementation of current costs and costs of ensuring expanded reproduction. Financial resources generate cash, as well as part of the cash used by the company in non-fund form. It is investigated that financial resources are a material expression of financial relations at the level of economic entities. Financial resources generate cash, as well as part of the cash used by the organization in non-fund form. The article is devoted to the study of the problems of management of financial resources of enterprises in the conditions of growing uncertainty and substantiation of the expediency of using the scenario method to the planning of financial resources. It is investigated that financial resources form the financial support of operating and investment activities of the enterprise. Financial planning is considered as one of the effective tools for managing the financial resources of the enterprise. It was found that in times of crisis forecasting should be based on the scenario method. Features of formation of information base for construction of scenarios of development of the company are considered. The "driving forces" of enterprise development are highlighted, namely the amount of equity, which forms the production capacity (expected element) and the need (volume) for borrowed funds (key uncertainty). It is proposed to develop 2 development scenarios in the context of financial resources management of the enterprise, namely "stable" and "crisis". The principles of enterprise financial management in conditions of increasing uncertainty are proposed.